COVID-19 and Long-Term Care Home Regulations in Canada Comparing Ontario and British Columbia - Karagach, Nicole (Université d'Ottawa | University of Ottawa, 2021)
This paper will explore the role of regulatory standards in LTC to try and understand why the COVID-19 virus had such devastating effects within Canada. Specifically, Ontario and British Columbia will be used as two case studies to answer the following three-part research question: What, if any, are the long-term care (LTC) regulatory differences between Ontario and British Columbia? If there are differences, 1) do these regulatory differences help explain the differentiating COVID-19 outcomes in LTC facilities within each province? And 2) do they help explain the relationship between COVID-19 in LTC facilities and ownership status within Ontario and British Columbia? The paper will first explore LTC broadly in Canada, including an overview of COVID-19 within the country. Next, the paper will provide a brief history of LTC and current regulations and enforcement within Ontario and British Columbia. Third, the paper provides an overview of COVID-19 outcomes within LTC throughout the various waves of the pandemic. These sections also include a brief discussion on pre-pandemic emergency preparedness and personal protective equipment (PPE) shortages within each province. The analysis section will then compare the research gathered within each section and point to the differences seen when comparing the two jurisdictions. The paper concludes by using the analysis findings to answer the research question and introducing new avenues of exploration for future research.